ORAL TRADITION AS A LEARNING RESOURCE FOR STRENGTHENING STUDENTS' LANGUAGE AND CULTURAL LITERACY IN SCHOOLS - Khairil Hadi; Dazrullisa Dazrullisa; Ali Salim Ali Razaq (Sensei International Journal of Education and Linguistic, 2025)
Indonesia has many oral traditions such as folktales, proverbs, and traditional songs, but in schools these are rarely used because the teachers usually only use the textbook. Actually oral tradition can be used as a learning resource for language and also for culture. This study discusses oral tradition as a learning resource for language and cultural literacy. The study used a mixed-method design with an experimental class and a control class. The data were collected through a test, observation, interview, and journal. The result shows that the experimental class is better than the control class and the students are more interested and also know more about their own culture. Therefore, teachers are suggested to use oral tradition in language learning.